1971
DOI: 10.1042/bj1240845
|View full text |Cite
|
Sign up to set email alerts
|

The specificity of combination between ristocetins and peptides related to bacterial cell wall mucopeptide precursors

Abstract: The affinity of ristocetin B for analogues of the C-terminal tripeptide sequence of bacterial cell wall mucopeptide precursors resembles that of vancomycin. Complex-formation requires a d-configuration in the two amino acid residues of the C-terminal dipeptide, an l-configuration is preferred in the preceding amino acid residue and positive charges on the peptide molecule decrease its affinity. The specificity of ristocetin B, however, differs from that of vancomycin in the requirements for the size of the sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
64
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 6 publications
9
64
0
Order By: Relevance
“…The mechanism by which ristocetin aggregates platelets is not yet known. Previous studies have shown that ristocetin inhibits the synthesis of peptidoglycans in bacterial cell walls either by steric interference with their polymerization or by forming stable complexes with mucopeptide precursors (25)(26)(27). Whether similar interactions with the platelet surface are involved in ristocetin-induced platelet aggregation remains to be determined.…”
Section: Discussionmentioning
confidence: 96%
“…The mechanism by which ristocetin aggregates platelets is not yet known. Previous studies have shown that ristocetin inhibits the synthesis of peptidoglycans in bacterial cell walls either by steric interference with their polymerization or by forming stable complexes with mucopeptide precursors (25)(26)(27). Whether similar interactions with the platelet surface are involved in ristocetin-induced platelet aggregation remains to be determined.…”
Section: Discussionmentioning
confidence: 96%
“…After paper electrophoresis, the major portion of the counts appeared to be linked to ristocetin, which is known to combine only with those peptides having a C-terminal D-D sequence (16 (Fig. 3).…”
Section: Methodsmentioning
confidence: 99%
“…A very small peak (_1%) was present in a position slightly more cathodal than the largest peak. Vancomycin (16) and a mol wt of 2,000 (17).…”
Section: Methodsmentioning
confidence: 99%